Pola Komunikasi Dakwah dalam Pembinaan Pemahaman Keagamaan Masyarakat Dusun Cikoneng Desa Cikoneng Kecamatan Ganeas Kabupaten Sumedang: Studi Kasus Masjid Al-Amin - Jihan Azhari; Bambang Saiful Ma'arif; Parihat Kamil (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. Da’wah is an effort to foster religious understanding in society. The function of dawah is to spread Islam to mankind as members of society, so that they have good morals and behavior according to Islamic guidance. The purpose of this study was to find out the da'wah agenda at Al-Amin Mosque in fostering religious understanding of the congregation, the congregation’s participation and response in da'wah activities, supporting and inhibiting factors in da’wah communication, and da'wah communication patterns in fostering religious understanding of the people of Cikoneng Hamlet, Cikoneng Village, Ganeas District Sumedang District. The method used in this research is a qualitative method with a descriptive qualitative research type. Data found through observation, interviews, and documentation. The informants in this study amounted to 8 people. The results of the study found that the pattern of da’wah communication used by the preacher in fostering religious understanding of the people of Cikoneng Hamlet, Cikoneng Village, Ganeas District (a case study at Al-Amin Mosque) is the pattern of group da’wah communication in the ta’lim assembly and Madrasah Diniyah, the pattern of interpersonal da’wah communication in hospitality to residents’ homes, and patterns of public da’wah communication in the implementation of compensation to people in need. The research was analyzed with Persuasive Communication Cognitive Learning Theory which is relevant according to the delivery of da’wah. Abstrak. Dakwah merupakan upaya untuk membina pemahaman keagamaan masyarakat. Fungsi dakwah adalah untuk penyebaran Islam kepada umat manusia sebagai anggota masyarakat, agar memiliki akhlak dan perilaku baik sesuai tuntunan Islam. Tujuan penelitian ini adalah untuk mengetahui agenda dakwah di Masjid Al-Amin dalam membina pemahaman keagamaan jamaah, partisipasi jamaah dan responnya dalam kegiatan dakwah, faktor penunjang dan penghambat dalam komunikasi dakwah, dan pola komunikasi dakwah dalam pembinaan pemahaman keagamaan masyarakat Dusun Cikoneng Desa Cikoneng Kecamatan Ganeas Kabupaten Sumedang. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan jenis penelitian kualitatif deskriptif. Data ditemukan melalui hasil observasi, wawancara, dan dokumentasi. Adapun informan dalam penelitian ini berjumlah 8 orang. Hasil penelitian menemukan bahwa, Pola komunikasi dakwah yang digunakan dai dalam pembinaan pemahaman keagamaan masyarakat Dusun Cikoneng Desa Cikoneng Kecamatan Ganeas (studi kasus Masjid Al-Amin) adalah pola komunikasi dakwah kelompok dalam majelis ta’lim dan Madrasah Diniyah, pola komunikasi dakwah antarpribadi dalam silaturahmi ke rumah warga, dan pola komunikasi dakwah publik dalam pelaksanaan santunan kepada masyarakat yang membutuhkan. Penelitian dianalisis dengan Teori Belajar Kognitif Komunikasi Persuasif yang relevan sesuai dengan penyampaian dakwah.